Правовий статус адвоката за Законом України «Про адвокатуру та адвокатську діяльність»: окремі питання врегулювання - Баєва, Н.; Baeva, N. (Східноєвропейський національний університет імені Лесі Українки, 2016)
В даній статті розглянуті окремі спірні питання набуття права на заняття адвокатською діяльністю, зокрема, щодо переліку робіт, які вважаються роботою за юридичною спеціальністю; терміну стажування; строку, який надається для складання кваліфікаційного іспиту особам, які не склали його; питання припинення права на заняття адвокатською діяльністю та дисциплінарної відповідальності адвоката. Автором зроблено пропозиції про внесення змін до Закону України «Про адвокатуру та адвокатську діяльність».article discusses some controversial issues of obtaining the right to practice law, in particular, those concerning the list of occupations which are considered to work in the legal specialty, among them the term of internship; the time that is given to a qualification exam for persons who have not passed it; termination of the right to practice law and disciplinary responsibilities of a lawyer. Stipulated by the law «On Advocacy and Advocate’s Practice» six months internship for a person who intends to become a lawyer, seems to be insufficient. According to the author, this term should be increased to at least twelve months. Author draws attention to the fact that according to the Law the Council of advocates is deprived of the right to take a decision as to the refusal to issue a certificate of the right to practice law due to a negative assessment of internship training. Unified educational process of acquiring legal profession at different stages is supervised by different legal institutions, which can hardly be considered appropriate. The law does not regulate the notification mechanism on the entry into force of a verdict against the lawyer issued by the Qualification-Disciplinary Bar Commission. The article lays emphasis on the importance of amending the Law of Ukraine «On Advocacy and Advocate’s Practice» with new provisions.
Legal Status of a Lawyer in the Law of Ukraine «On Advocacy and Advocate’s Practice»: Certain Issues of Adjustment.
Keywords: адвокат; стажист адвоката; дисциплінарна відповідальність адвоката; lawyer; trainee-lawyer; disciplinary liability of lawyer